Wear-resistant water-repellent amorphous alloy brake disc and manufacturing method thereof
By performing nitrogen atmosphere laser modification and low-temperature heating treatment on the amorphous alloy surface of the automobile brake disc, hardening and superhydrophobic effects are achieved, and the problem of insufficient wear resistance and water repellency of the brake disc is solved, extending the service life and improving driving safety.
Patent Information
- Application Number
- CN202411544711.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-25
AI Technical Summary
The wear resistance and water repellency of existing automobile brake disc materials are insufficient, resulting in reduced brake performance and short service life, especially in rainy and snowy weather conditions.
The surface hardening and superhydrophobic effect are achieved by laser modification and low-temperature heating treatment under nitrogen atmosphere on the surface of the amorphous alloy brake disc.
It significantly improves the wear resistance and water repellency of the brake disc, extends the service life, and improves the reliability of the brake system in rainy and snowy weather conditions, ensuring the driving safety of drivers and passengers.
Smart Images

Figure CN119506643A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of advanced surface treatment materials, and relates to a wear-resistant and water-repellent amorphous alloy brake disc and a manufacturing method thereof. The present invention provides a new method for improving the wear resistance and water-repellent properties of the brake disc, which helps to extend the service life of the automobile brake disc and improve the safety of the driver and passengers. Background Art
[0002] In the history of automobile development, safety has always been the focus of common concern of automobile manufacturers and consumers. The braking system is one of the core parts of vehicle safety, and its performance is directly related to whether the driver can slow down or stop in time and effectively, so as to avoid accidents and ensure driving safety. The brake disc is an important part of the automobile braking system. The specific way to achieve vehicle braking is: when the driver steps on the brake pedal, the brake pad in the brake caliper clamps the brake disc, and converts the kinetic energy of the vehicle into heat energy through friction, thereby achieving deceleration or stopping. Therefore, the brake disc must have sufficient wear resistance to withstand the long-term friction of the brake pad without easy wear. Gray cast iron is a commonly used material for manufacturing traditional brake discs, but gray cast iron has poor wear resistance and may show obvious wear in a short time, which will affect the flatness and braking performance of the brake disc, resulting in a weakened braking effect. As an emerging amorphous metal material, amorphous alloys have higher hardness than traditional crystalline alloys. Therefore, the application of amorphous alloys to automobile brake discs will help improve the wear resistance of the brake discs. In addition, in rainy, snowy or humid conditions, a water film is easily formed between the brake disc and the brake pad, which reduces the friction between the brake disc and the brake pad, resulting in an increase in braking distance and affecting driving safety. For this reason, a new method for manufacturing wear-resistant and water-repellent amorphous alloy brake discs is urgently needed to simultaneously improve the wear resistance and water-repellent properties of the brake discs, thereby extending the service life of the brake discs and improving the reliability of the brake system in rainy and snowy weather conditions, providing more reliable protection for the driving safety of drivers and passengers. Summary of the invention
[0003] The purpose of the present invention is to extend the service life of automobile brake discs and improve the reliability of automobile brake systems in rainy and snowy weather, thereby ensuring the driving safety of drivers and passengers, and providing a method for manufacturing wear-resistant and water-repellent amorphous alloy brake discs. The present invention achieves hardening and super-hydrophobicity on the surface of the amorphous alloy brake disc simultaneously by regulating the laser irradiation parameters in a nitrogen atmosphere, as well as the temperature and time of the subsequent low-temperature heating treatment, thereby solving the problem that the prior art cannot simultaneously improve the wear resistance and water repellency of the amorphous alloy brake disc.
[0004] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0005] In order to solve the above technical problems, the present invention is implemented by adopting the following technical solutions:
[0006] A method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc comprises the following steps:
[0007] (1) Manufacturing of amorphous alloy brake discs: manufacturing amorphous alloy brake discs through thermoplastic forming technology;
[0008] (2) Construction of micro-nano composite structure and introduction of hardening phase: placing the amorphous alloy brake disc prepared in step (1) into a nitrogen atmosphere chamber, performing laser modification on the surface of the amorphous alloy brake disc to obtain a laser nitrided surface having a micro-nano composite structure;
[0009] (3) Constructing a synchronously hardened and super-hydrophobic surface: The laser nitrided surface with a micro-nano composite structure in step (2) is subjected to low-temperature heating treatment to obtain a synchronously hardened and super-hydrophobic surface.
[0010] Furthermore, the purity of nitrogen used in step (2) is 90%-99.99%, the pressure of the nitrogen atmosphere chamber is maintained at 0.005MPa-0.05MPa, and the laser used is a fiber laser with a wavelength of 532nm-1064nm and a beam quality M 2 <1.6, the diameter of the laser in the focal plane is 40-50μm, the laser pulse width and repetition frequency are 100-300ns and 50-100kHz respectively, the laser multi-line overlap method is used to irradiate the amorphous alloy surface, the laser scanning speed is 10-100mm / s, the scanning interval is 2-10μm, and the laser power density is 2.7×10 11 -1.2×10 12 W / m 2 .
[0011] Preferably, the purity of nitrogen used is 99.99%, the pressure of the nitrogen atmosphere chamber is maintained at 0.01 MPa, the laser used is a fiber laser, the wavelength is 1064 nm, the diameter of the laser in the focal plane is 43 μm, the laser pulse width and repetition frequency are 230 ns and 50 kHz respectively, the laser multi-line overlap method is used to irradiate the surface of the amorphous alloy, the laser scanning speed is 50 mm / s, the scanning interval is 4.3 μm, and the laser power density is 2.7×10 11 -1.2×10 12 W / m 2 ;
[0012] Preferably, the laser power density is 1.2×10 12 W / m 2 .
[0013] Furthermore, the temperature of the heating treatment in step (3) is 100-200° C., and the time of the heating treatment is 1-5 hours.
[0014] Preferably, the temperature of the heating treatment is 200° C., and the time of the heating treatment is 1 hour.
[0015] Furthermore, the material used for manufacturing the amorphous alloy brake disc by thermoplastic forming technology in step (1) is a zirconium-based or titanium-based amorphous alloy.
[0016] A wear-resistant and water-repellent amorphous alloy brake disc is manufactured by the method described above.
[0017] Furthermore, the wear-resistant and water-repellent amorphous alloy brake disc is made of a zirconium-based or titanium-based amorphous alloy.
[0018] Further, the brake disc has a synchronously hardened and super-hydrophobic surface.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The present invention can not only effectively slow down the wear and failure of automobile brake discs and reduce the frequency of brake disc replacement, thereby reducing vehicle maintenance costs and the cost of replacing parts, but also inhibit the formation of water film between the brake disc and the brake pad in rainy and snowy weather, ensuring that the brake disc and the brake pad are in full contact, thereby providing better braking control for the vehicle and enhancing driving safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings:
[0022] Figure 1 A schematic diagram of an amorphous alloy brake disc manufactured by the present invention through thermoplastic forming technology;
[0023] Figure 2This is a schematic diagram of the laser irradiation test under nitrogen atmosphere of the present invention;
[0024] Figure 3 A diagram of the laser power density parameters used in the present invention;
[0025] Figure 4 This is a scanning electron microscope morphology image of the laser irradiated surface in a nitrogen atmosphere of the present invention;
[0026] Figure 5 The three-dimensional topography of the laser irradiated surface in the nitrogen atmosphere of the present invention;
[0027] Figure 6 This is a test diagram of chemical composition of the surface irradiated by laser in a nitrogen atmosphere of the present invention;
[0028] Figure 7 The contact angle statistics of the original surface of the amorphous alloy and the laser nitrided surface of the amorphous alloy of the present invention;
[0029] Figure 8 It is a hardness statistical diagram of the original surface of the amorphous alloy and the laser nitrided surface of the amorphous alloy of the present invention;
[0030] Fig. 9 This is a schematic diagram of the pin-on-disc friction and wear test of the present invention;
[0031] Fig.10 The scanning electron microscope morphology images of the original surface of the amorphous alloy of the present invention and the surface of the amorphous alloy after the friction and wear test of the synchronously hardened and super-hydrophobic amorphous alloy;
[0032] Fig.11 The three-dimensional morphology of the original surface of the amorphous alloy of the present invention and the surface of the amorphous alloy after the friction and wear test of the synchronously hardened and super-hydrophobic amorphous alloy;
[0033] Fig.12 The wear volume statistics of the original surface of the amorphous alloy after the friction and wear test of the present invention, and the surface of the synchronously hardened and super-hydrophobic amorphous alloy;
[0034] Fig.13 Schematic diagram of mechanical scratch test on the original surface of the amorphous alloy and the surface of the synchronously hardened and super-hydrophobic amorphous alloy of the present invention;
[0035] Fig.14 The graphs are the changes of the surface contact angle with the mechanical scratching distance of the original surface of the amorphous alloy of the present invention and the surface of the synchronously hardened and super-hydrophobic amorphous alloy after mechanical scratching;
[0036] Fig.15 The present invention is a flow chart of a method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. In the drawings, the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The described embodiments are part of the embodiments of the present invention, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limitations on the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The embodiments of the present invention are described in detail below in conjunction with the drawings.
[0038] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the scope of protection of the present invention.
[0039] The present invention is described in detail below in conjunction with the accompanying drawings:
[0040] The purpose of the present invention is to extend the service life of automobile brake discs and improve the reliability of automobile brake systems in rainy and snowy weather, thereby ensuring the driving safety of drivers and passengers, and providing a method for manufacturing wear-resistant and water-repellent amorphous alloy brake discs. The present invention achieves hardening and super-hydrophobicity on the surface of the amorphous alloy brake disc simultaneously by regulating the laser irradiation parameters in a nitrogen atmosphere, as well as the temperature and time of the subsequent low-temperature heating treatment, thereby solving the problem that the prior art cannot simultaneously improve the wear resistance and water repellency of the amorphous alloy brake disc.
[0041] The amorphous alloy brake disc is prepared by thermoplastic forming technology, and then the surface of the amorphous alloy brake disc is laser modified in a nitrogen atmosphere, and then the amorphous alloy brake disc is subjected to low-temperature heating treatment. The heating treatment temperature is 100-200°C and the heating treatment time is 1-5 hours.
[0042] The material used to manufacture the amorphous alloy brake disc by thermoplastic forming technology can be zirconium-based or titanium-based amorphous alloy.
[0043] The purity of nitrogen is 90%-99.99%, the pressure of nitrogen atmosphere chamber is maintained at 0.005MPa-0.05MPa, the laser used is fiber laser, the wavelength is 532nm-1064nm, the beam quality is M 2<1.6, the diameter of the laser in the focal plane is 40-50μm, the laser pulse width and repetition frequency are 100-300ns and 50-100kHz respectively, the laser multi-line overlap method is used to irradiate the amorphous alloy surface, the laser scanning speed is 10-100mm / s, the scanning interval is 2-10μm, and the laser power density is 2.7×10 11 -1.2×10 12 W / m 2 .
[0044] After low-temperature heating treatment of the laser-modified surface in a nitrogen atmosphere, the surface friction and wear volume can be reduced by 89.5% compared with the original surface of the amorphous alloy, and the surface still has superhydrophobic properties after mechanical scratching for 1000 cm.
[0045] Example 1: Preparation of a nitrided super-hydrophobic surface on the surface of a zirconium-based amorphous alloy brake disc
[0046] Step 1: Manufacture amorphous alloy brake discs by thermoplastic forming technology, such as Figure 1 As shown;
[0047] Step 2: Place the amorphous alloy brake disc in a nitrogen atmosphere chamber, and then perform laser modification on the surface of the amorphous alloy brake disc, such as Figure 2 As shown, the purity of nitrogen used is 99.99%, and the pressure of the nitrogen atmosphere chamber is maintained at 0.01MPa. The wavelength of the laser used is 1064nm, the laser pulse width and repetition frequency used are 230ns and 50kHz respectively, and the laser multi-line overlap method is used to irradiate the surface of the amorphous alloy. The laser scanning speed is 50mm / s, the scanning interval is 4.3μm, and the laser power density of Case 1-6 is 2.7×10 11 -1.2×10 12 W / m 2 Specific laser power density parameters are as follows: Figure 3 shown. Figure 4 and Figure 5 The SEM morphology and 3D morphology of the laser irradiated surface (case 1-6) under nitrogen atmosphere respectively show that the laser irradiated surface under nitrogen atmosphere has a micro-nano composite structure and a nitride phase is introduced on the surface ( Figure 6 ), the surface of amorphous alloy brake disc has been laser nitrided;
[0048] Step 3: The laser nitrided surface with micro-nano composite structure was subjected to low temperature heating treatment at a temperature of 200°C for 1 hour. The wettability of the original surface of the amorphous alloy and the laser nitrided surface after heating treatment was further tested. 5 μL of deionized water was used to measure the contact angle of the sample surface. The average of the contact angles at 5 different positions on the surface of each sample was taken to determine the contact angle of the surface. Figure 7 As shown in the figure, the contact angle of the original surface of the amorphous alloy is less than 90°, and the original surface of the amorphous alloy is in a hydrophilic state, while the contact angle of the laser nitrided surface after heating treatment (Case 4-6) can be greater than 150°, and the laser nitrided surface achieves super-hydrophobicity. It can be seen that after laser irradiation in a nitrogen atmosphere and subsequent low-temperature heating treatment, the surface of the amorphous alloy brake disc can achieve simultaneous nitridation and super-hydrophobicity.
[0049] Example 2: Nanoindentation Test
[0050] Nanoindentation tests were performed on the original surface of the amorphous alloy and the laser nitrided surface in step 2 of Example 1, using a loading-unloading method, with an indentation load of 150 mN and a loading rate of 10 mN / s. During the nanoindentation test, a pyramid diamond indenter with an angle of 115° between the edge and the surface was used, and the data was analyzed using embedded software based on the Oliver-Pharr method. To ensure the accuracy of the sample surface hardness, 5 indentation tests were performed on each sample surface, and the average hardness was taken. The test results are shown in Figure 2. Figure 8 As shown in the figure, the hardness of the original surface of the amorphous alloy is 6.64±0.19GPa, and the hardness of the laser nitrided surface (Case 6) can reach 13.97±0.43GPa. Compared with the hardness of the original surface of the amorphous alloy, the hardness of the laser nitrided surface (Case 6) can be increased by 110%.
[0051] Example 3: Friction and wear test
[0052] The friction and wear tests were carried out on the original surface of the amorphous alloy, and the synchronously hardened and super-hydrophobic amorphous alloy surface (Case 6). The test method was pin-on-disk. The Si3N4 ball was used as the pin, the original surface of the amorphous alloy, and the synchronously hardened and super-hydrophobic amorphous alloy surface were used as the disk. Fig. 9 As shown. The load of the friction and wear test is 4N, the Si3N4 ball is fixed, the rotation speed of the original amorphous alloy surface, and the synchronously hardened and super-hydrophobic amorphous alloy surface is 500r / min, and the friction and wear test time is 30min. After the friction and wear test, argon gas is used to blow the friction and wear debris away from the sample surface, and then the friction and wear track is observed using a scanning electron microscope and a laser confocal microscope. Fig.10As shown, it can be seen that there are obvious differences in the microscopic morphology of the original surface of the amorphous alloy, and the wear track of the synchronously hardened and super-hydrophobic amorphous alloy surface. The original surface of the amorphous alloy has obvious furrows, and there are more particles on the wear track, indicating that obvious abrasive wear has occurred on the original surface of the amorphous alloy. In the process of abrasive wear, the particles act as third-body abrasive particles between the pin sample and the disc sample in the form of sliding or rolling, which will cause damage to the disc sample. In addition, the vibration generated by the disc sample during rotation will cause the pin sample and the disc sample to continuously collide and separate. When the third-body abrasive particles enter between the two and collide, high-stress wear will occur. This high stress similar to impact will aggravate the wear of the disc sample. Compared with the wear track of the original surface of the amorphous alloy, the wear track of the synchronously hardened and super-hydrophobic amorphous alloy surface has fewer particles and appears in layers. This layer can act as a lubricant to slow down the wear of the disc sample.
[0053] The three-dimensional morphology of the original surface of the amorphous alloy and the synchronously hardened and super-hydrophobic amorphous alloy surface after wear was further measured. Fig.11 The three-dimensional morphology and profile of the surface after the friction and wear test. The wear track of the original surface of the amorphous alloy presents a typical V-shaped groove with a depth of 34μm and a width of 1269μm. Compared with the original surface of the amorphous alloy, the depth of the groove is reduced to 9μm and the width is reduced to 832μm after the friction and wear test of the synchronously hardened and super-hydrophobic amorphous alloy surface.
[0054] In order to quantitatively compare and analyze the friction and wear resistance of the sample surfaces, the wear volume of the original amorphous alloy surface after the friction and wear test, as well as the synchronously hardened and super-hydrophobic amorphous alloy surface, was measured. To ensure the accuracy of the test results, two more sets of friction and wear tests were conducted on the original amorphous alloy surface, as well as the synchronously hardened and super-hydrophobic amorphous alloy surface under the same conditions. Fig.12 The wear volume statistics of the original surface of the amorphous alloy after the friction and wear test, as well as the synchronous hardening and super-hydrophobic amorphous alloy surface, show that the wear volume of the sample is closely related to the hardness of the material surface. The wear volume of the original surface of the amorphous alloy with a smaller surface hardness is larger, and its value is (5.522±0.136)×10 5 μm 3 , while the wear volume of the synchronously hardened and super-hydrophobic amorphous alloy with larger surface hardness is smaller, and its value is (0.580±0.056)×10 5 μm 3 Compared with the original amorphous alloy surface, the friction and wear volume of the synchronously hardened and super-hydrophobic amorphous alloy surface (Case 6) is reduced by 89.5%. It can be seen that by introducing the nitride phase on the surface of the amorphous alloy brake disc, the friction and wear resistance of the amorphous alloy brake disc is significantly improved.
[0055] Example 4: Water repellency test after mechanical scratching
[0056] It can be seen from Example 3 that the friction and wear resistance of the amorphous alloy brake disc with the introduction of the nitride phase is significantly improved compared to the original amorphous alloy brake disc. In addition, the water repellency of the automobile brake disc also plays a vital role in the safety of the driver and passengers. The water repellency of the original surface of the amorphous alloy, as well as the synchronously hardened and super-hydrophobic amorphous alloy surface (Case 6) under mechanical load was further tested. In order to simulate the working condition of the brake disc in constant friction, the original surface of the amorphous alloy, as well as the synchronously hardened and super-hydrophobic amorphous alloy surface are fixed to the bottom of the weight, and then the sample surface is directly contacted with the silicon carbide sandpaper, and then the weight is pushed to reciprocate in the horizontal direction, such as Fig.13 The area of the original amorphous alloy surface and the synchronously hardened and superhydrophobic amorphous alloy surface is 1 cm 2 , the weight is 100g, the mesh number of silicon carbide sandpaper is 1500 mesh, and the reciprocating distance is 10cm. According to the above method, the original surface of the amorphous alloy, as well as the synchronously hardened and super-hydrophobic amorphous alloy surface are reciprocated mechanically scratched on the sandpaper, and the contact angles of the surfaces at different mechanical scratching distances are recorded.
[0057] like Figure 7 As shown in the figure, the contact angle of the original surface of the amorphous alloy is less than 90°, so the amorphous alloy is inherently hydrophilic. According to the classic Wenzel wetting model:
[0058] cosθ W =rcosθ Y
[0059] Among them, θ Y is the contact angle of the liquid on an ideal smooth surface, θ W is the contact angle of the liquid on the rough surface, and r is the roughness factor of the solid surface, that is, the ratio of the actual contact area between the liquid and the solid surface to the projected area on the solid surface. Therefore, for the surface of rough materials, the value of r is greater than 1, and then the original amorphous alloy surface will become more hydrophilic after mechanical scratching. Therefore, according to the classic Wenzel wetting model, the hydrophilicity of the surface of the amorphous alloy brake disc will increase after mechanical scratching, which will intensify the formation of water film between the brake disc and the brake pad in rainy and snowy weather, and then reduce the friction between the brake disc and the brake pad, affecting the driving safety of the driver and passengers. The above is an analysis based on the classic Wenzel wetting model, and further experimental results also verified that mechanical scratching will increase the hydrophilicity of the surface of the amorphous alloy brake disc. Fig.14As shown in the figure, as the mechanical scratching distance of the original surface of the amorphous alloy on the silicon carbide sandpaper increases, its surface contact angle shows a trend of gradually decreasing. When the mechanical scratching distance reaches 1000cm, the contact angle of the original surface of the amorphous alloy decreases from 85.2±1.5° to 38.6±1.9°. However, after 1000cm of mechanical scratching, the surface contact angle of the synchronously hardened and super-hydrophobic amorphous alloy surface (Case 6) is greater than 150°, and it still has super-hydrophobic properties. Obviously, compared with the original surface of the amorphous alloy, the synchronously hardened and super-hydrophobic amorphous alloy surface still has excellent water-repellent properties after mechanical scratching.
[0060] The present invention provides a new method for simultaneously improving the wear resistance and water repellency of automobile brake discs. The specific steps are as follows: Fig.15 On the one hand, the present invention can effectively reduce the wear and failure of the automobile brake disc, thereby extending the service life of the automobile brake disc, and on the other hand, it can improve the reliability of the automobile braking system under rainy and snowy weather conditions, providing more reliable protection for the driving safety of drivers and passengers.
[0061] Example 5
[0062] The present invention provides a wear-resistant and water-repellent amorphous alloy brake disc, which is manufactured by a manufacturing method of a wear-resistant and water-repellent amorphous alloy brake disc provided by the present invention. The material is a zirconium-based or titanium-based amorphous alloy; it has synchronous hardening and a super-hydrophobic surface; the specific manufacturing method comprises the following steps:
[0063] Step 1: manufacturing an amorphous alloy brake disc by thermoplastic forming technology;
[0064] Step 2: placing the amorphous alloy brake disc prepared in step 1 into a nitrogen atmosphere chamber, and performing laser modification on the surface of the amorphous alloy brake disc to obtain a laser nitrided surface having a micro-nano composite structure;
[0065] The purity of nitrogen used was 99.99%, the pressure of nitrogen atmosphere chamber was maintained at 0.01MPa, the laser used was fiber laser, the wavelength was 1064nm, the beam quality was M 2 <1.6, the diameter of the laser in the focal plane is 43μm, the laser pulse width and repetition frequency are 230ns and 50kHz respectively, the laser multi-line overlap method is used to irradiate the amorphous alloy surface, the laser scanning speed is 50mm / s, the scanning interval is 4.3μm, and the laser power density is 2.7×10 11 -1.2×10 12 W / m 2 ;
[0066] Step 3: Perform low-temperature heating treatment on the laser nitrided surface with micro-nano composite structure in step 2 to obtain a synchronously hardened and super-hydrophobic surface. The heating treatment temperature is 200° C. and the heating treatment time is 1 hour.
[0067] After the above three steps, a wear-resistant and water-repellent amorphous alloy brake disc according to the embodiment of the present invention is obtained, and the hardness of the laser nitrided surface is increased by 110% compared with the hardness of the original amorphous alloy surface. After the friction and wear test of the synchronous hardening and super-hydrophobic surface, the surface wear volume is reduced by 89.5% compared with the original surface of the amorphous alloy, and the contact angle of the surface is greater than 150° after the 1000cm mechanical scratch test, and it still has super-hydrophobic properties, while the contact angle of the original surface of the amorphous alloy is reduced from 85.2±1.5° to 38.6±1.9° after the 1000cm mechanical scratch test.
[0068] In summary, the present invention provides a new method for simultaneously improving the wear resistance and water repellency of automobile brake discs. On the one hand, the present invention can effectively slow down the wear and failure of automobile brake discs, thereby extending the service life of automobile brake discs. On the other hand, it can improve the reliability of automobile braking systems under rainy and snowy weather conditions, providing more reliable protection for the driving safety of drivers and passengers.
[0069] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent replacement and improvement made by any person skilled in the art within the technical scope disclosed by the present invention and within the spirit and principle of the present invention shall be covered within the protection scope of the present invention. At the same time, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc, characterized in that: The steps include: (1) Manufacturing of amorphous alloy brake discs: manufacturing amorphous alloy brake discs through thermoplastic forming technology; (2) Construction of micro-nano composite structure and introduction of hardening phase: placing the amorphous alloy brake disc prepared in step (1) into a nitrogen atmosphere chamber, performing laser modification on the surface of the amorphous alloy brake disc to obtain a laser nitrided surface having a micro-nano composite structure; (3) Constructing a synchronously hardened and super-hydrophobic surface: The laser nitrided surface with a micro-nano composite structure in step (2) is subjected to low-temperature heating treatment to obtain a synchronously hardened and super-hydrophobic surface.
2. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 1, characterized in that: The purity of nitrogen used in step (2) is 90%-99.99%, the pressure of the nitrogen atmosphere chamber is maintained at 0.005MPa-0.05MPa, and the laser used is a fiber laser with a wavelength of 532nm-1064nm and a beam quality M 2 <1.6, the diameter of the laser in the focal plane is 40-50μm, the laser pulse width and repetition frequency are 100-300ns and 50-100kHz respectively, the laser multi-line overlap method is used to irradiate the amorphous alloy surface, the laser scanning speed is 10-100mm / s, the scanning interval is 2-10μm, and the laser power density is 2.7×10 11 -1.2×10 12 W / m 2 .
3. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 2, characterized in that: The purity of nitrogen used was 99.99%, and the pressure of the nitrogen atmosphere chamber was maintained at 0.01 MPa. The laser used was a fiber laser with a wavelength of 1064 nm. The diameter of the laser at the focal plane was 43 μm. The laser pulse width and repetition frequency were 230 ns and 50 kHz, respectively. The laser multi-line overlap method was used to irradiate the surface of the amorphous alloy. The laser scanning speed was 50 mm / s, the scanning interval was 4.3 μm, and the laser power density was 2.7×10 11 -1.2×10 12 W / m 2 .
4. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 2, characterized in that: The laser power density is 1.2×10 12 W / m 2 .
5. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 1, characterized in that: The temperature of the heating treatment in step (3) is 100-200° C., and the time of the heating treatment is 1-5 hours.
6. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 5, characterized in that: The temperature of the heat treatment was 200° C., and the time of the heat treatment was 1 hour.
7. The method for manufacturing a wear-resistant and water-repellent amorphous alloy brake disc according to claim 1, characterized in that: The material used for manufacturing the amorphous alloy brake disc by thermoplastic forming technology in step (1) is zirconium-based or titanium-based amorphous alloy.
8. A wear-resistant and water-repellent amorphous alloy brake disc, characterized in that: The method is manufactured by any one of claims 1 to 7.
9. The wear-resistant and water-repellent amorphous alloy brake disc according to claim 8, characterized in that: The material is zirconium-based or titanium-based amorphous alloy.
10. The wear-resistant and water-repellent amorphous alloy brake disc according to claim 8, characterized in that: The brake disc has a synchronously hardened and super-hydrophobic surface.